Formation of the Concept of the Cost Management of the Enterprises of Road Economy Формирование концепции управления издержками предприятий дорожного хозяйства - Lysenko Alina A. (Bìznes Inform, 2012)
The article is devoted to formation of the basic theoretical positions of the concept of the cost management of the enterprises of road sector, which is based on general methodology of the theory of management. Within the developed concept have been disclosed the connections between subject and object of the cost management and the scientific-methodical tools. The stages of its implementation have been defined, expressed in the development of three separate models. Статья посвящена вопросам формирования основных теоретических положений концепции управления издержками предприятий дорожного хозяйства, которая базируется на общей методологии теории управления. В пределах разработанной концепции раскрыта связь между субъектом и объектом управления издержками, указан научно-методический инструментарий, а также выделены этапы ее реализации, выраженные в разработке трех отдельных моделей.